2018
DOI: 10.1039/c8sc00633d
|View full text |Cite
|
Sign up to set email alerts
|

Red-emissive azabenzanthrone derivatives for photodynamic therapy irradiated with ultralow light power density and two-photon imaging

Abstract: Azabenzanthrone derivatives with high phototoxicity and efficient emission are designed for photodynamic therapy and deep-tissue imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Meanwhile, studies have shown that in the aggregate states, AIE PSs are able to offer effective 1 O 2 production . Encapsulating AIE PSs into nanoparticles (NPs) using amphipathic polymers as the matrix endows them with good water dispersibility and biocompatibility, which allows them to be applied in both imaging and photosensitization functions 10a,13. In addition, it has been demonstrated that well‐designed AIE PS NPs exhibit good photostability and low dark toxicity, which can be spontaneously excreted after PDT by the stool with little side effects based on pharmacokinetics results …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, studies have shown that in the aggregate states, AIE PSs are able to offer effective 1 O 2 production . Encapsulating AIE PSs into nanoparticles (NPs) using amphipathic polymers as the matrix endows them with good water dispersibility and biocompatibility, which allows them to be applied in both imaging and photosensitization functions 10a,13. In addition, it has been demonstrated that well‐designed AIE PS NPs exhibit good photostability and low dark toxicity, which can be spontaneously excreted after PDT by the stool with little side effects based on pharmacokinetics results …”
Section: Introductionmentioning
confidence: 99%
“…S25 †), which is usually observed in D-A type compounds. 46,47 The intensied PL intensity is due to the formation of aggregates, representing a typical AIE signature. The AIE amplitude increases from MTPE-TP1 to MTPE-TP3, especially there is a notable enhancement for MTPE-TP3, which is likely due to the more twisted molecular geometry and inhibition of intermolecular interactions in the aggregate state.…”
Section: Resultsmentioning
confidence: 99%
“…Worthy of note, homoleptic zinc(II) dipyrromethene complexes and large organic aromatic systems, which were encapsulated with the same polymer matrix but with different terminal group were also found mostly in the lysosomes. [108][109][110] Following this, the cellular uptake mechanism of NP in A549 cells was investigated. As there is a higher demand for biotin in rapidly growing cells than in healthy cells, biotin and its conjugates are rapdily internalized by the sodium multivitamin transporter (SMVT), which is overexpressed in a variety of cancers.…”
Section: Resultsmentioning
confidence: 99%